The influence of MNC’s culture on employee’s work life balance - Guessous, Oumeima (My University, 2014)
This study deals with two major issues from the business field and especially the HR one. The aim of the thesis is to analyze both concepts of work life balance and MNC’s culture in order to understand the link between the two. Finding a balance between work and life spheres have been an important issue for nowadays’ HR studies and in a globalized world economy as ours, the understanding of the structure and organization of a MNC is necessary. The objectives of the study are more precisely to determine the different components of each concept and then understand the impact of MNC’s culture on the employees’ perception of work life balance. The theoretical part of the study is based on the existing literature of work life balance and MNCs culture. The research method followed is a qualitative approach. The empirical data was gathered by conducting 12 semi-structured interviews and collecting data existing within an IT consulting MNC, the HQ of which are in France and the subsidiaries in Belgium and Morocco. The empirical data collected were analyzed and paralleled with the assumptions of the theoretical part in order to draw conclusions. The findings of the study showed that the MNC’s culture does influence the employees’ perception of work life balance since it is part of this culture and it designs the way employees’ perceive the company and its organization. The way the MNC promote this balance and insist on its importance influence on the one hand the employees’ perception of this balance and on the other hand allows them to actually reach this balance. It also appears that the MNC’s culture is not the only parameter to take into account when trying to understand the employees’ perception of work life balance. This concept is complex and three spheres should be considered when dealing with it: work, family and personal/social activities.
Keywords: Work Life Balance; Multinational Corporations Culture; Gender; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|